2021
DOI: 10.1111/omi.12336
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and neutrophil responses to Porphyromonas gingivalis in human whole blood

Abstract: Porphyromonas gingivalis is a causative agent for periodontal disease. Binding of platelets to this gram-negative anaerobe can regulate host hemostatic (thrombus forming) and immune (neutrophil interacting) responses during bacterial infection. Additionally, in response to bacterial pathogens neutrophils can release their DNA, forming highly prothrombotic neutrophil extracellular traps (NETs), which then further enhance platelet responses. This study evaluates the role of P. gingivalis on platelet expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Preincubating whole blood with live Porphyromonas gingivalis results in increased platelet–neutrophil interactions in the presence or absence of added ADP [ 172 ]. However, the highest interaction levels are observed in the presence of ADP stimulation, even for the shortest P. gingivalis preincubation time of 5 min.…”
Section: Nets and Platelet Functionsmentioning
confidence: 99%
“…Preincubating whole blood with live Porphyromonas gingivalis results in increased platelet–neutrophil interactions in the presence or absence of added ADP [ 172 ]. However, the highest interaction levels are observed in the presence of ADP stimulation, even for the shortest P. gingivalis preincubation time of 5 min.…”
Section: Nets and Platelet Functionsmentioning
confidence: 99%
“…However, platelet aggregation depends on the ratio of platelet/bacteria, consistent with the possibility of either a threshold phenomenon or multiple competing platelet interactions. In whole blood, platelet expression of CD62P, an adhesion molecule expressed on surfaces of activated platelets, increases following preincubation of high P. gingivalis colony-forming units (CFU) with or without subsequent ADP stimulation [ 263 ]. Conversely, there is a trend towards higher CD62P expression even in response to low P. gingivalis CFU, particularly as preincubation time is extended.…”
Section: The Role Of Gingipains In Platelet Functionmentioning
confidence: 99%
“…Platelet-neutrophil interactions are believed to be mediated by an interaction between platelet P-selectin and neutrophil P-selectin glycoprotein ligand-1 (PSGL-1) [ 269 ]. Such interaction is enhanced following ADP-mediated platelet activation [ 263 ]. Platelet-neutrophil interactions are also enhanced in the presence of P. gingivalis in a preincubation time-dependent manner.…”
Section: The Role Of Gingipains In Platelet Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets activated by P. gingivalis express P-selectin on their surface, which binds to the receptor P-selectin glycoprotein-1 on leukocytes, forming platelet-leukocyte aggregates that not only converge a variety of leukocytes (neutrophils, monocytes) to the site of inflammation and clear bacteria but also induce a coagulation-inflammatory series of responses ( 224 ). Further studies have indicated that P. gingivalis induces increased platelet-neutrophil aggregate formation, enhances platelet-neutrophil interactions, and induces the release of NETs, which in turn promotes late thrombosis in AS ( 225 , 226 ). However, no studies on the effects of P. gingivalis on other types of leukocyte-platelet interactions have been seen.…”
Section: Immune Mechanism Of P Gingivalis To Promo...mentioning
confidence: 99%